AR technology-assisted selfie design and dissemination path analysis - Zhang, Di; Alsagoff, Syed Agil; Yasin, Megat Al Imran; Razi, Siti Aishah Muhammad (Redfame Publishing, 2023)
Augmented reality (AR) is a technology based on 3D registration, virtual-real fusion and human-computer interaction to achieve the integration of virtual objects and real scenes. The core problem of augmented reality task is the accurate and fast recognition and tracking of objects in real scenes, which provides the technical basis for updating and optimizing the selfie design. This paper discusses the specific technical path of AR applied to selfie design based on the deep learning approach, and demonstrates the impact of different deep learning algorithms on the effectiveness of the integration of AR and selfie, and finally the paper discusses the application prospects of AR in selfie.